2009
DOI: 10.1113/jphysiol.2009.172023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reduced end‐tidal carbon dioxide tension on cerebral blood flow during heat stress

Abstract: Passive heat stress reduces arterial carbon dioxide partial pressure (P aCO 2 ) as reflected by 3 to 5 Torr reductions in end-tidal carbon dioxide tension (P ETCO 2 ). Heat stress also reduces cerebrovascular conductance (CBVC) by up to 30%. While P aCO 2 is a strong regulator of CBVC, it is unlikely that the relatively small change in P ETCO 2 during heating is solely responsible for the reductions in CBVC. This study tested the hypothesis that P aCO 2 , referenced by P ETCO 2 , is not the sole mechanism for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
116
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 42 publications
8
116
2
Order By: Relevance
“…3 In addition, it is well known that heat stress modifies distribution of blood flow toward cutaneous circulation while decreasing renal and splanchnic blood flows by enhanced vasoconstriction. 15,19 Maintained or decreased cerebral blood velocity during heat stress has been reported [10][11][12][20][21][22][23] but the mechanism remains unclear. The present study demonstrated that CBF conductance in MCAV mean , ICA, and VA gradually decreased during whole body heating, whereas CVC forehead and ECA conductance increased by 3 times and 2.5 times from the baseline, respectively.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 In addition, it is well known that heat stress modifies distribution of blood flow toward cutaneous circulation while decreasing renal and splanchnic blood flows by enhanced vasoconstriction. 15,19 Maintained or decreased cerebral blood velocity during heat stress has been reported [10][11][12][20][21][22][23] but the mechanism remains unclear. The present study demonstrated that CBF conductance in MCAV mean , ICA, and VA gradually decreased during whole body heating, whereas CVC forehead and ECA conductance increased by 3 times and 2.5 times from the baseline, respectively.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 99%
“…However, their follow-up study showed that MCAV mean did not return to the baseline level during heat stress (internal temperature increased by 1.41C) even when P ET CO 2 was clamped to the preheating. 11,12 In the present study, we also calculated the relationship between changes in P ET CO 2 and changes in ICA and VA blood flows throughout heat stress, but there was no significant relationship. We did not perform any perturbation to change P ET CO 2 in this study.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using end-tidal carbon dioxide tension (PET CO 2 ) to estimate Pa CO 2 during passive heat stress (i.e., increase in internal temperature ϳ1.2-1.5°C) suggest that heat stress reduces Pa CO 2 ϳ4 -8 mmHg (3,5,15,26). A potential limitation to these studies is the assumption that PET CO 2 is an accurate surrogate for Pa CO 2 , the latter being the physiologically relevant variable.…”
mentioning
confidence: 99%